ديناميكية حماية البيئة ضمن اتفاقيات ومؤتمرات المنظمة العالمية للتجارة - عابى، وليد; عزي، الأخضر أبو علاء (جامعة زيان عاشور بالجلفة, 2018)
تناولت الدراسة موضوع حماية البيئة ضمن اتفاقية الجات والمنظمة العالمية للتجارة، باستعراض سبل حماية البيئة والعلاقة بين تحرير التجارة الخارجية وحماية البيئة، فضلاً عن دراسة مراحل تحرير التجارة في ظل اتفاقيات الجات 1947 والمنظمة العالمية للتجارة، كما هدفت الدراسة إلى التعرف على أهم مراحل تطور حماية البيئة في الجات والمنظمة العالمية للتجارة، وآثار هذه الحماية على تنافسية صادرات الدول النامية، وكذا دور لجنة التجارة والبيئة في المساهمة في الحفاظ علي البيئة وحمايتها دون أن تكون لهذه الحماية انعكاسات سلبية علي صادرات الدول النامية، وأهم النتائج المتوصل إليها من خلال اللجنة في المؤتمرات الوزارية للمنظمة. The study deals with the protection of the environment under the GATT and the World Trade Organization, which deals with the protection of the environment as well as the relationship between the liberalization of foreign trade and the protection of the environment, as well as studying the stages of trade analysis under the GATT 1947 and the World Trade Organization. The development of environmental protection in the GATT and the World Trade Organization and the effects of such protection on the competitiveness of exports of developing countries, as well as the Committee on Trade and Environment in contributing to the protection and protection of the environment without such protection having negative repercussions on the exports of developing countries. The results reached by the Committee in the Organization Ministerial Conferences.
Keywords: منظمة التجارة العالمية -- حماية البيئة -- التجارة الخارجية -- الاتفاقيات الدولية -- اتفاقية الجات